Compensating differentials for occupational health and safety risks - Kniesner, Thomas J.,Viscusi, W. Kip (IZA - Institute of Labor Economics, 2022)
The most enduring measure of how individuals make personal decisions affecting their health and safety is the compensating wage differential for job safety risk revealed in the labor market via hedonic equilibrium outcomes. The decisions in turn reveal the value of a statistical life (VSL), the value of a statistical injury (VSI), and the value of a statistical life year (VSLY), which have both mortality and morbidity aspects that we describe and apply here. All such tradeoff rates play important roles in policy decisions concerning improving individual welfare. Specifically, we explicate the recent empirical research on VSL and its related concepts and link the empirical results to the on-going examinations of many government policies intended to improve individuals' health and longevity. We pay special attention to recent issues such as the COVID pandemic and newly emerging foci on distributional consequences concerning which demographic groups may benefit most from certain regulations.
10419/252241
Keywords: Graue Literatur; value of statistical life; VSL; value of statistical injury; VSI; value of a statistical life year; VSLY; mortality risk; morbidity risk; benefit cost analysis; hedonic labor market equilibrium; compensating wage differential; evaluation of health and safety programs